Smart machines, Remote Sensing, Precision Farming, Processes, Mechatronic, Materials and Policies for Safety and Health Aspects - Massimo Cecchini (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
The introduction of "smart machines" for agricultural operations will allow several advantages, such as an increase in their efficiencies, a reduction in environmental impacts and a reduction of work injuries. There are partially- and fully-automatic devices for most aspects of agricultural functions, from seeding and planting to harvesting and postharvesting, from spraying to livestock management, and so on The objectives of this book are: study of man-machine dialogue systems; analysis on towed or carried machines: forestry chippers, manure spreaders, round balers and others; safety and health management system design and engineering; safety and health monitoring sensors and sensing; data-driven methods for anomaly detection, diagnosis and prognosis; precision farming; mechatronic; automotive and agriculture machinery applications; engineering of hybrid and integrated systems and their efficiency maximization, especially for safety and health purposes, aimed to injuries and accidents reduction, use of remote sensor and mechatronic systems applied in several aspects.